Sweet cream butter - Caldwell, R. E.; Wright, A. H. (My University, 1908)
Introduction: Experiment stations of late years have been working upon the subject of flavor and keeping quality of butter. They have taken up the subject of the bacterial content of milk, ripening of cream by control of temperature, and control by commercial starters, but practically no work has been done with regard to producing sweet cream butter.
Citation: Caldwell, R. E. and Wright, A. H. Sweet cream butter. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Butter; Sweet Cream; Food Science; Graduating theses; Senior theses; Theses